Bifunctional catalyst as well as preparation method and application thereof

By loading single-atom Ag and nanoAg clusters on the surface of the support, a bifunctional catalyst was prepared, which solved the problem of low oxidation and reduction activity of hydrogen peroxide in the prior art, and achieved the effect of efficient degradation of tetracycline in wastewater.

CN119869618AActive Publication Date: 2025-04-25NANKAI UNIV

Patent Information

Application Number
CN202510040987.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-25
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

Prior art In complex sewage environments, hydrogen peroxide has low redox activity and cannot effectively degrade organic pollutants that are difficult to degrade.

Method used

By loading single-atom Ag and nanoAg clusters on the surface of the support, a dual function of synthesis of hydrogen peroxide and efficient degradation of tetracycline in wastewater was prepared.

Benefits of technology

The concentration of the catalyst in photosynthesis of hydroxyl radicals is significantly higher than that of other catalysts, and has higher reactivity. It can completely degrade tetracycline in wastewater within 10 minutes, with a degradation rate of up to 0.36 min-1.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869618A_ABST
    Figure CN119869618A_ABST
Patent Text Reader

Abstract

The invention discloses a bifunctional catalyst and a preparation method and application thereof, and relates to the technical field of catalytic materials, the bifunctional catalyst comprises a carrier and monatomic Ag and nano Ag clusters dispersed on the carrier, and the catalyst is obtained by loading the monatomic Ag and the nano Ag clusters on the surface of the carrier. The bifunctional catalyst has the dual functions of synthesizing hydrogen peroxide and efficiently degrading tetracycline in sewage, meanwhile, the concentration of photosynthesis hydroxyl radicals of the bifunctional catalyst is remarkably higher than that of other catalysts, higher reaction activity is achieved, tetracycline in the sewage can be completely degraded within 10 min, and the degradation rate reaches 0.36 min <-1 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalytic materials, and in particular to a bifunctional catalyst and a preparation method and application thereof. Background Art

[0002] In recent years, in the cutting-edge research field of modern sewage treatment technology, photocatalytic oxygen reduction reaction has become an important direction with great application potential due to its unique reaction mechanism and environmentally friendly characteristics. This has far-reaching significance for promoting the development of sewage treatment technology towards a green and efficient direction.

[0003] In the related art, a catalyst is used to catalyze oxidation to form hydrogen peroxide, and then the generated hydrogen peroxide is used to remove organic pollutants in sewage. Although hydrogen peroxide has a certain redox activity, its redox activity is still low in a complex sewage environment and cannot degrade various organic pollutants that are difficult to degrade.

[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention

[0005] The technical task of the present application is to address the above deficiencies and provide a bifunctional catalyst and its preparation method and application. The present application obtains a catalyst by loading single-atom Ag and nano-Ag clusters on the surface of a carrier, which has the dual functions of synthesizing hydrogen peroxide and efficiently degrading tetracycline in wastewater.

[0006] To achieve the above objectives, this application provides the following technical solutions:

[0007] According to one aspect of the present application, a bifunctional catalyst is provided, comprising: a carrier and single-atom Ag and nano-Ag clusters dispersed on the carrier.

[0008] In some embodiments, the carrier is polyheptadiazine imide.

[0009] In some embodiments, the loading amount of Ag on the carrier is 0.5-5 wt %.

[0010] According to another aspect of the present application, a method for preparing a bifunctional catalyst is also provided, comprising: adding NaBH4 to an AgNO3 solution and stirring for 1 min, then adding polyheptadiazine imide and stirring for 3 to 5 h, filtering after stirring, and drying the filtered solid matter at 40°C to 60°C for 6 to 12 h to obtain a bifunctional catalyst with coexistence of single-atom Ag and nano-Ag clusters on the surface.

[0011] In some embodiments, the concentration of the AgNO3 solution is 0.05-0.5 mg / mL.

[0012] In some embodiments, the ratio of the added amounts of the AgNO 3 solution, the NaBH 4 and the polyheptazinonimide is 10 ml: 0.1 mg: 100 mg.

[0013] In some embodiments, the preparation method of the polyheptadiazine imide includes: mixing lithium chloride, potassium chloride and graphite phase carbon nitride in a mortar to obtain a mixture; placing the mixture in a crucible, heating the crucible to 400-600°C at a heating rate of 5-10°C / min in an air environment, keeping warm for 2-4 hours, then washing with water at 60°C-80°C for 2-4 hours, filtering, and drying the filtered solid matter at 40°C-60°C for 6-12 hours to obtain the polyheptadiazine imide.

[0014] In some embodiments, the mass ratio of the lithium chloride, the potassium chloride, and the graphite-phase carbon nitride is 4.5:5.5:1.

[0015] According to another aspect of the present application, there is also provided an application of a bifunctional catalyst in the synthesis of hydrogen peroxide by photo- and electro-catalytic oxygen reduction and an application of a bifunctional catalyst in the photocatalytic degradation of tetracycline.

[0016] In some embodiments, the photocatalytic degradation of tetracycline is photocatalytic degradation of tetracycline in wastewater.

[0017] Compared with the prior art, the advantages and positive effects of the present application are: the catalyst obtained by loading single-atom Ag and nano-Ag clusters on the surface of the carrier has the dual functions of synthesizing hydrogen peroxide and efficiently degrading tetracycline in wastewater.

[0018] Furthermore, the concentration of photosynthetic hydroxyl radicals in the bifunctional catalyst was significantly higher than that of other catalysts, and it had a higher reactivity, which could completely degrade tetracycline in sewage within 10 minutes, with a degradation rate of up to 0.36 minutes. -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1The microstructure images of the bifunctional catalyst in Example 1 of the present application are shown, wherein a is a TEM morphology image, b is a high-resolution lattice photo, and c is a spherical aberration correction image;

[0021] Figure 2 The XRD patterns of the catalysts in Example 1 and Comparative Examples 1-3 of the present application are shown;

[0022] Figure 3 The synchrotron radiation spectra of the catalysts in Example 1 and Comparative Examples 2-3 of the present application are shown, where a is the X-ray absorption near-edge structure and b is the fitting result of the R space;

[0023] Figure 4 The XPS spectra of the catalysts in Example 1 and Comparative Examples 1-3 of the present application are shown;

[0024] Figure 5 The photosynthetic hydrogen peroxide performance diagram of the catalysts in Example 1 and Comparative Examples 1-3 of the present application is shown;

[0025] Figure 6 The photosynthesis·OH performance diagram of the catalysts in Example 1 and Comparative Examples 1-3 of the present application is shown;

[0026] Figure 7 The photocatalytic degradation performance graph of tetracycline of the catalysts in Example 1 of the present application and Comparative Examples 1-3 is shown. DETAILED DESCRIPTION

[0027] In order to more clearly understand the above-mentioned purposes, features and advantages of the present application, the present application is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

[0028] The present application is further described below in conjunction with the accompanying drawings and specific embodiments.

[0029] Example 1: Preparation of a bifunctional catalyst with coexistence of single-atom Ag and nano-Ag clusters on the surface, the specific steps are as follows:

[0030] S100, preparation of polyheptazinonimide (PHI): lithium chloride, potassium chloride and graphite phase carbon nitride are mixed evenly in a mortar, and the mass ratio of lithium chloride, potassium chloride and graphite phase carbon nitride is 4.5:5.5:1. The mixture is placed in a crucible, heated to 550°C at a heating rate of 5°C / min in air, and kept warm for 4 hours. Then, it is placed in 80°C water for 2 hours, filtered and dried at 40°C for 12 hours, and finally PHI is obtained.

[0031] S200, preparation of bifunctional catalyst with coexistence of single-atom Ag and nano-Ag clusters on the surface (PHI-Ag SA / NC ):

[0032] 0.1 mg of NaBH4 was added to 10 ml of 0.2 mg / mL AgNO3 aqueous solution and stirred for 1 min, then mixed with 100 mg of PHI and stirred for 3 h, then filtered and dried at 60 °C for 12 h to obtain PHI-Ag with coexistence of surface Ag atoms / clusters. SA / NC catalyst.

[0033] Comparative Example 1: PHI was prepared using the method in S100 of Example 1.

[0034] Comparative Example 2: Preparation of Ag-atom dispersed PHI catalyst PHI-Ag SA .

[0035] 100 mg of PHI obtained in Comparative Example 1 was dispersed in 100 ml of water, then mixed with a 2 mg / mL silver nitrate solution, stirred for 0.5 h, filtered, and dried at 40 ° C for 12 h to finally obtain a PHI catalyst PHI-Ag dispersed with Ag atoms. SA .

[0036] Comparative Example 3: Preparation of PHI Catalyst PHI-Ag with Dispersed Ag Clusters NC。

[0037] 50 μL of polyethyleneimine was added to 1 ml of 2 mg / mL silver nitrate solution and stirred, and then 5 μL of formaldehyde solution was added and stirred overnight to obtain an Ag cluster solution; 100 mg of PHI obtained in Comparative Example 1 was dispersed in 100 ml of water, and the Ag cluster solution was added and stirred for 3 h, then filtered, and dried at 40° C. for 6 to 12 h to finally obtain a PHI catalyst PHI-Ag with Ag clusters dispersed therein. NC .

[0038] Figure 1 The microstructure images of the bifunctional catalyst in Example 1 of the present application are shown, wherein a is a TEM morphology image, b is a high-resolution lattice photo, and c is a spherical aberration correction image. Figure 1 As shown, the lattice fringes can be clearly seen through the TEM morphology image and the high-resolution lattice photograph, indicating that the catalyst has been successfully synthesized; through the spherical aberration corrected image, it can be clearly observed that the Ag clusters and single-atom Ag have been successfully loaded on the PHI surface, among which the yellow dotted line accurately circles the position of the Ag clusters, and the red solid line circles the location of the single-atom Ag.

[0039] Figure 2 The XRD patterns of the catalysts in Example 1 and Comparative Examples 1-3 of the present application are shown. Figure 2As shown in the figure, the characteristic peaks at 8° and 27° correspond to the (100) and (002) crystal planes of PHI, respectively, which once again indicates the successful preparation of PHI; and after the loading of Ag clusters and single-atom Ag, the XRD pattern of the catalyst did not show obvious changes, which means that the loading process did not have a substantial impact on the crystal structure of PHI.

[0040] Figure 3 The synchrotron radiation spectra of the catalysts in Example 1 and Comparative Examples 2-3 of the present application are shown, where a is the X-ray absorption near-edge structure and b is the fitting result of the R space. Figure 3 As shown, single-atom Ag has been successfully loaded on PHI-Ag SA Ag clusters have also been successfully loaded on PHI-Ag NC superior.

[0041] Figure 4 The XPS spectra of the catalysts in Example 1 and Comparative Examples 1-3 of the present application are shown. Figure 4 As shown, the signal peak of Ag was detected at 370 nm, proving that Ag had been successfully loaded on the PHI surface.

[0042] The catalysts obtained in Example 1 and Comparative Examples 1-3 were tested for photosynthetic hydrogen peroxide. The specific method was as follows: 25 mg of the catalyst was dispersed in 50 ml of water, 5 ml of isopropanol was added, and after ultrasonic dispersion, oxygen was introduced. The reaction was carried out under 300 W xenon light for 10 min. Every 2 min, 1 mL of the reaction solution was added to 1 mL of 0.4 M KI solution and 1 mL of 0.1 M potassium hydrogen phthalate solution. After standing for 20 min, the absorbance change of the mixed solution was detected at 350 nm using a spectrophotometer to test the performance of photocatalytic oxygen reduction synthesis of hydrogen peroxide.

[0043] Figure 5 The photosynthetic hydrogen peroxide performance diagram of the catalysts in Example 1 and Comparative Examples 1-3 of the present application is shown. Figure 5 As shown, PHI-Ag NC The ability of the catalyst to synthesize hydrogen peroxide is significantly higher than that of other catalysts, and its hydrogen peroxide production is as high as 550μM, which means that PHI-Ag NC The catalyst plays a significant role in promoting the synthesis of hydrogen peroxide.

[0044] The catalysts obtained in Example 1 and Comparative Examples 1-3 were tested for the concentration of photosynthetic hydroxyl radicals (·OH). The specific method was to disperse 25 mg of the catalyst in 50 ml of a 0.1 mM terephthalic acid solution, disperse it evenly through ultrasonication, and then react it under 300 W xenon light. The concentration of terephthalic acid was detected by liquid chromatography, and the concentration of photocatalytic synthesis of ·OH was tested.

[0045] Figure 6 The photosynthesis·OH performance diagram of the catalysts in Example 1 and Comparative Examples 1-3 of the present application is shown. Figure 6 As shown, PHI-Ag SA / NC The concentration of photosynthetic OH in the catalyst was significantly higher than that of other catalysts, and PHI-Ag SA The catalyst is second, PHI-Ag NC The catalyst is relatively poor, that is, the successful loading of Ag clusters can significantly improve the ability of the catalyst to photosynthesize ·OH.

[0046] The catalysts obtained in Example 1 and Comparative Examples 1-3 were tested for photocatalytic degradation of tetracycline. The specific method was to disperse 25 mg of the catalyst in 50 ml of a 20 ppm tetracycline solution, disperse it evenly by ultrasonication, and then react it under 300 W xenon light. The concentration of tetracycline was detected by liquid chromatography to test the photocatalytic degradation performance of tetracycline.

[0047] Figure 7 The photocatalytic degradation performance diagram of tetracycline in Example 1 and Comparative Examples 1-3 of the present application is shown. Figure 7 As shown, PHI-Ag SA / NC The catalyst can completely degrade tetracycline within 10 minutes, with a degradation rate of up to 0.36 minutes. -1 This is because hydroxyl radicals are one of the important active species in the process of photocatalytic degradation of organic matter. SA / NC The catalyst can photosynthesize more ·OH, thus having higher reactivity. At the same time, hydrogen peroxide and ·OH can act together on organic matter to achieve more efficient degradation.

[0048] It should be noted that the catalyst in this embodiment can be selected and used according to different actual application scenarios. For example, when the catalyst is used in an application scenario with the synthesis of hydrogen peroxide as the main goal, a catalyst with only single-atom Ag loaded on the surface can be selected. When the catalyst is used in an application scenario with sewage treatment as the main goal, a catalyst that simultaneously loads single-atom Ag and Ag clusters is used to meet actual needs, thereby ensuring that in different usage scenarios, the best application effect can be achieved by reasonably selecting catalysts.

[0049] Through the above specific implementations, those skilled in the art can easily implement the present application. However, it should be understood that the present application is not limited to the above specific implementations. Based on the disclosed implementations, those skilled in the art can arbitrarily combine different technical features to achieve different technical solutions.

Claims

1. A bifunctional catalyst, characterized in that: include: A carrier and single-atom Ag and nano-Ag clusters dispersed on the carrier.

2. A bifunctional catalyst according to claim 1, characterized in that: The carrier is polyheptadiazine imide.

3. A bifunctional catalyst according to claim 1, characterized in that: The loading amount of Ag on the carrier is 0.5-5 wt %.

4. The method for preparing a bifunctional catalyst according to claim 2, characterized in that: include: NaBH4 is added to the AgNO3 solution and stirred for 1 minute, then polyheptazinonimide is added and stirred for 3 to 5 hours, and filtered after stirring. The filtered solid matter is dried at 40°C to 60°C for 6 to 12 hours to obtain a bifunctional catalyst with coexistence of single-atom Ag and nano-Ag clusters on the surface.

5. The method for preparing a bifunctional catalyst according to claim 4, characterized in that: The concentration of the AgNO3 solution is 0.05-0.5 mg / mL.

6. The method for preparing a bifunctional catalyst according to claim 4, characterized in that: The ratio of the added amounts of the AgNO3 solution, the NaBH4 and the polyheptadiazine imide is 10 ml: 0.1 mg: 100 mg.

7. The method for preparing a bifunctional catalyst according to claim 4, characterized in that: The preparation method of the polyheptazinonimide comprises: Mixing lithium chloride, potassium chloride and graphite phase carbon nitride in a mortar to obtain a mixture; The mixture is placed in a crucible, and the crucible is heated to 400-600°C at a heating rate of 5-10°C / min in an air environment, kept warm for 2-4 hours, then washed with water at 60-80°C for 2-4 hours, filtered, and the filtered solid matter is dried at 40-60°C for 6-12 hours to obtain the polyheptadiazine imide.

8. The method for preparing a bifunctional catalyst according to claim 7, characterized in that: The mass ratio of the lithium chloride, the potassium chloride and the graphite-phase carbon nitride is 4.5:5.5:

1.

9. Use of a bifunctional catalyst according to any one of claims 1 to 3 in the synthesis of hydrogen peroxide by photo- and electro-catalytic oxygen reduction and in the photocatalytic degradation of tetracycline.

10. The use according to claim 9, characterized in that: The photocatalytic degradation of tetracycline is photocatalytic degradation of tetracycline in sewage.

Citation Information

Patent Citations

  • Two-dimensional material supported monatomic doped Au24M bimetallic cluster electrocatalyst

    CN113782756A

  • Preparation method of copper cluster-based metal organic framework material with photo-Fenton-like catalytic performance for rapid photo-degradation of dye / antibiotic

    CN115212924A

  • Carbon-based platinum monatomic nano-enzyme as well as preparation method and application thereof

    CN115957323A

  • Titanium dioxide supported ruthenium catalyst, preparation method and halogenated organic matter treatment application

    CN116832807A

  • Au single atom and Pt sub-nanocluster co-loaded catalyst as well as preparation method and application thereof

    CN118403630A

Cited By

  • Method for photocatalytic degradation of bisphenol A and generation of H2O2 based on O-ZnIn2S4

    CN122164439A